DELIMITĂRI CONCEPTUALE, SENSURI ŞI CLASIFICĂRI ALE NOŢIUNII DE VALOARE - USM ADMIN (Moldova State University, 2007)
In this article I have related concepts, meanings and classifications of the notion of value. In the specialized literature there is a multitude of criteria of classification and delimitation of this concept. These criteria are named differently by diverse authors but they frequently have an identical elucidation. It is worth mentioning the fact that there is necessary a clear interpretation of these delimitations, systematizations and classifications to contribute at the correct and adequate cognition of this notion.